Assessing the profitability of hybrid coconut farms in the Second District of Bohol, Philippines - TRESHA NADINE Q. PILAYRE; MERLYN G. BUSCATO; JENFER MARIE M. GASATAN; ETHEL ZEAN M. AÑOSA (Smujo International, 2026)
Abstract. Pilayre TNQ, Buscato MG, Gasatan JMM, Añosa EZM. 2026. Assessing the profitability of hybrid coconut farms in the Second District of Bohol, Philippines. Asian J Agric 10: g100115. https://doi.org/10.13057/asianjagric/g100115. Hybrid coconut farming has emerged as a promising innovation to revitalize the coconut industry and improve smallholder livelihoods in the Philippines, yet its economic performance under real farm conditions remains insufficiently documented. This study assessed the profitability of hybrid coconut farms in the Second District of Bohol, where hybrid varieties are being promoted amid early bearing stages and ongoing post-Typhoon Odette recovery in 2021. Using a descriptive research design, data were gathered from 63 farmer-respondents through semi-structured interviews and questionnaires. Respondents had an average age of 57.13±11.21 years and farming experience of 19±12.38 years, cultivating farms averaging 1.34±1.72 hectares. Cost and return analysis, explicitly excluding imputed family labor to reflect cash-based profitability, revealed an average yield of 57 nuts per tree per year and a net income of ₱10,608.33 per hectare, with a Benefit-Cost Ratio (BCR) of 2.14. The modest profitability observed is primarily attributed to the early bearing stage of hybrid trees and the lingering impact of Typhoon Odette, which reduced farm productivity. Despite these constraints, hybrid coconut production remains economically viable and holds potential for increased profitability as plantations mature. Findings highlight the need for targeted interventions such as capacity building, input subsidies, and climate-resilient management practices to enhance productivity and income stability. Overall, the study provides empirical evidence to guide policymakers, investors, and development planners in promoting a sustainable and inclusive hybrid coconut industry in the Philippines.